Beyond Comorbidity: A Critical Perspective of Syndemic Depression and Diabetes in Cross‐cultural Contexts. (15th May 2015) - Mendenhall, Emily
Abstract : This article examines the comorbidity concept in medical anthropology. I argue that the dearth of articles on comorbidity in medical anthropology may result from the rise of syndemic theory. Syndemics recognize how social realities shape individual illness experiences as well as distribution of diseases across populations. I discuss synergistic interactions foundational to the syndemics construct through my research of depression and diabetes comorbidity in vulnerable populations from urban United States, India, and South Africa. I argue that social and economic factors that cluster with depression and diabetes alone and together exemplify the biosocial processes that are at the heart of syndemics. In doing so, I illustrate how social, cultural, and economic factors shape individual‐level experiences of co‐occurring diseases despite similar population‐level trends. Finally, I discuss the relevance of syndemics for the fields of medicine and public health while cautioning what must not be lost in translation across disciplines.